2023
DOI: 10.1088/1361-6552/acc5cf
|View full text |Cite
|
Sign up to set email alerts
|

The death of the short-form physics essay in the coming AI revolution

Abstract: The latest AI language modules can produce original, high quality full short-form (300-word) Physics essays within seconds. These technologies such as ChatGPT and davinci-003 are freely available to anyone with an internet connection. In this work, we present evidence of AI generated short-form essays achieving First-Class grades on an essay writing assessment from an accredited, current university Physics module. The assessment requires students answer five open-ended questions with a short, 300-word essay ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(34 citation statements)
references
References 11 publications
2
29
0
3
Order By: Relevance
“…Chatbots, like ChatGPT, are an artificial intelligence resource that have diverse potential uses by instructors and students, such as being used to create assignments or to provide the learner with feedback and explanations. , ChatGPT’s functionality as an automated feedback system parallels that of other systems but with superior natural language processing (NLP) ability. Nascent research into its use in the chemistry , and physics education research communities have examined its ability to answer questions, produce explanations, and contribute to written work like lab reports.…”
Section: Introductionmentioning
confidence: 99%
“…Chatbots, like ChatGPT, are an artificial intelligence resource that have diverse potential uses by instructors and students, such as being used to create assignments or to provide the learner with feedback and explanations. , ChatGPT’s functionality as an automated feedback system parallels that of other systems but with superior natural language processing (NLP) ability. Nascent research into its use in the chemistry , and physics education research communities have examined its ability to answer questions, produce explanations, and contribute to written work like lab reports.…”
Section: Introductionmentioning
confidence: 99%
“…ChatGPT was then found to excel in short-form physics essays, i.e. perform on par with students [168]. Instruction with ChatGPT could increase students' perception of ChatGPT, and it is expected that ChatGPT can play an important role in instruction [30,33].…”
Section: Utilizing Llmsmentioning
confidence: 99%
“…Contrary to some literature emerging on this topic that stipulates plagiarism detection software is ineffective in detecting ChatGPT generated content (e.g., Gleason, 2022), ChatGPT itself indicates that software exists that is sensitive to ChatGPT generated text (OpenAI, 2023). A team of investigators in the United Kingdom investigated, running student short form essay responses through the plagiarism software Grammarly and TurnitIn with scores of 2% ± 1% and 7% ± 2%, respectively (Yeadon et al, 2022). Based on these scores and the favourable grading that these essays received, these authors concluded that ChatGPT is a major threat to fidelity in their academic context.…”
Section: The Integration Stancementioning
confidence: 99%